Urgensi Formulasi Besaran Minimal Honorarium Notaris Dalam Undang-Undang Jabatan Notaris - Aju Putrijanti; Fadhilla Neyma Salshabilla (Magister Kenotariatan Universitas Diponegoro, 2023)
AbstractThe determination of notary honorarium constitutes an essential factor of cost imposition for client or people who want to use notary service, base to determine the maximum honorarium accorded to economical and sociological values as explained in Article 36 of Act No. 2 of 2014 about Notary Public Job but there is no base to determine the minimum honorarium of notary. This research used juridical empirical research as the method, the specification is descriptive-analytical. The urgency to determine the minimum honorarium of notary should be considered because there is no base to determine the minimum honorarium of a Notary Public in Law No. 2 of 2014 about Notary Public Job, as well as sanctions for violations of honorarium of a notary. Honorarium is expected to have a clear base in order to support the professionalism of notary public. The formulation of minimum basic honorarium that is ideal for notaries is to add formulations in Article 36 of Law No. 2 of 2014 to mention the determination of the minimum amount of honorarium determined by the organization of notary positions contained in the Notary Code of Ethics in accordance with their respective regions by also considering several factors.Keywords: notary: honorarium; formulationAbstrakPenentuan honorarium notaris merupakan faktor penting bagi pengenaan biaya untuk klien atau orang yang menggunakan jasa notaris, dasar menentukan maksimal honorarium notaris yang dibebankan pada klien diberikan sesuai dengan nilai ekonomis dan sosiologis sebagaimana tercantum dalam Pasal 36 Undang-Undang Nomor 2 Tahun 2014 tentang Jabatan Notaris tetapi tidak ada dasar untuk menentukan minimal honorarium notaris. Metode yang digunakan adalah penelitian hukum yuridis empiris, spesifikasi artikel ini adalah deskriptif analitis. Urgensi untuk menentukan minimal honorarium notaris harus dipertimbangkan karena tidak adanya dasar untuk menentukan honorarium minimum notaris dalam Undang-Undang Nomor 2 Tahun 2014 tentang Jabatan Notaris, begitu juga dengan sanksi atas pelanggaran honorarium notaris. Honorarium diharapkan memiliki dasar yang jelas untuk mendukung profesionalisme notaris. Formulasi honorarium minimal dalam Undang-Undang Nomor 2 Tahun 2014 yang ideal bagi notaris adalah dengan menambahkan Formulasi dalam Pasal 36 Undang-Undang Nomor 2 Tahun 2014 agar juga menyebutkan penetapan besaran minimal honorarium yang ditentukan oleh organisasi jabatan notaris tertuang di dalam Kode Etik Notaris sesuai dengan daerah masing-masing dengan juga mempertimbangkan beberapa faktor.Kata kunci: notaris; honorarium; formulasi